Electrochemical, surface and quantum chemical studies of novel imidazole derivatives as corrosion inhibitors for J55 steel in sweet corrosive environment - Singh A.; Ansari K.R.; Kumar A.; Liu W.; Songsong C.; Lin Y. (My University, 2025)
The corrosion inhibition performance of three novel imidazole derivatives namely 2-(4-methoxyphenyl)-4,5-diphenyl-imidazole (M-1), 4,5-diphenyl-2-(p-tolyl)-imidazole (M-2) and 2-(4-nitrophenyl)-4,5-diphenyl-imidazole (M-3) for J55 steel in CO2 saturated brine solution was studied by weight loss method, electrochemical impedance spectroscopy (EIS), potentiodynamic polarization, scanning electrochemical microscopy (SECM), contact angle, scanning electron microscope (SEM), atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS) and quantum chemical calculation. M-1 exhibited the best inhibition efficiency of 93% at 400 mg/L concentration. The adsorption of the imidazole derivatives obeyed the Langmuir adsorption isotherm. Contact angle measurement reveals the hydrophobic nature of J55 steel in presence of inhibitors. Quantum chemical calculation well supports the experimental results. © 2017 Elsevier B.V.